Personality, purpose, and wellbeing: a comparison of Iranian and U.S. telecommuters during the COVID-19 pandemic - Abaei, Elnaz; Ameli Renani, Zahra; Lester, David (Frontiers in Psychology, 2026)
The present study compared employees in Iran and the United States to examine whether personality traits predicted sense of purpose and wellbeing during telecommuting in the COVID-19 pandemic. A total of N = 142 participants were included (73 Iranian employees in Iran; 69 U.S. employees in the United States). Personality was assessed using the Myers–Briggs Type Indicator (MBTI), and purpose and wellbeing were measured with validated scales. Descriptive analyses showed that Iranian participants scored higher on the Sensing dimension, with no other mean differences or gender effects. Regression analyses indicated that Extraversion significantly predicted sense of purpose (β = 0.387, p < 0.01, R2 = 0.305) and wellbeing (β = 0.515, p < 0.001, R2 = 0.260) among Iranian workers, whereas Judging marginally predicted purpose (β = 0.263, p < 0.10, R2 = 0.128) and wellbeing (β =0.227, p < 0.10, R2 = 0.136) among U.S. workers. Overall, personality–outcome associations were modest in both groups, and mean levels of purpose and wellbeing did not differ across countries. This study contributes to cross-cultural telework research by highlighting culturally specific links between personality and psychological functioning during a global crisis.